A wide-bandgap polymer based on the alkylphenyl-substituted benzo[1, 2-b:4, 5-b′]dithiophene unit with high power conversion efficiency of over 11%. Issue 34 (15th August 2018) - Guo, Xia; Li, Wanbin; Guo, Huan; Guo, Bing; Wu, Jingnan; Ma, Wei; Zhang, Maojie; Wong, Wai-Yeung
Abstract : A novel wide bandgap polymer PTZP with E optg of 2.01 eV was designed and synthesized. PSCs based on PTZP exhibited high PCE of 11.8%. PCEs of over 10% were obtained with an active layer thickness of 200 nm or an area of 0.81 cm 2 . PTZP was shown to be a promising conjugated polymer for the fabrication of efficient large area PSCs. Abstract : A novel wide-bandgap conjugated polymer (PTZP) based on alkylphenyl-substituted benzo[1, 2- b :4, 5- b ′]dithiophene (BDT-P) as the electron-rich unit and thiazolo[5, 4- d ]thiazole (TTz) as the electron-deficient unit was designed and synthesized for the non-fullerene polymer solar cell (PSCs) application. The polymer exhibited a wide bandgap of 2.01 eV with a strong absorption in the range of 300–620 nm, which was complementary with that of the fused-ring small molecule acceptor (SMA; 2, 2′-((2 Z, 2′ Z )-((4, 4, 9, 9-tetrahexyl-4, 9-dihydro- s -indaceno[1, 2- b :5, 6- b ′]dithiophene-2, 7-diyl)bis(methanylylidene))bis(3-oxo-2, 3-dihydro-1 H -indene-2, 1-diylidene))dimalononitrile, IDIC). Also, the polymer exhibits a deep highest occupied molecular orbital (HOMO) energy level of −5.41 eV. Furthermore, the polymer film possesses strong crystallinity and dominated face-on stacking with a small d -spacing of 3.65 Å, resulting in a high hole mobility of 4.01 × 10 −3 cm 2 V −1 s −1 . The optimal PSCs based on the PTZP:IDIC blend showed a high PCE of 11.8% with an open-circuit voltage ( V oc ) of 0.90 V, a short-circuit current density ( J sc ) of 17.9 mA cm −2 and a fill factor (FF) of 73.3%. Moreover, the device with an active layer thickness of up to 200 nm or area of up to 0.81 cm 2 exhibited outstanding performance, with PCE of over 10%, resulting from the excellent molecular stacking. These results revealed that PTZP will be a promising conjugated polymer for the fabrication of efficient large-area PSCs.